Collected traditions and scattered secrets. Eclecticism and esotericism in the works of the 14th century ashkenazi kabbalist Menahem Ziyyoni of Cologne - Laura, Heidi (Nordisk judaistik/Scandinavian Jewish Studies, 1999)
There are many examples of authors of mystical works who consciously chose to retreat the role of copyists and collectors of already existing traditions. The emphasis in Kabbalistic works is on recording mystical tradition, while personal reports of mystical experiences or clearly individual expositions of mystical themes are rarely found in the large corpus of Kabbalistic works. This article attempts to illuminate the special place of mosaic works and collectanea in Kabbalistic literature and its specific character, using the works of an unjustly neglected 14th century kabbalist as a focus. The writings of Ashkenazi kabbalist Menahem Ziyyoni are exemplary of the problem of collected works. Kabbalistic anthological works had an especially golden period in the 14th century. The mosaic works of the 14th century became a new way of continuing the zoharic project of an overarching hermeneutical system, which integrated and legitimated a number of different interpretations of the same text.